The theoretical concept of determining the critical point of crisis processes in the socio-economic system - E. R. Romanova; V. S. Stel’Makh (Управление)
From the position of the modern theory of crisis management, a hypothesis of the presence of a critical point in the development of a socio-economic system has proposed. Depending on the severity of the crisis, limited resources and time, the relationship between the degree of controllability and destructible system has considered. The degree of crisis affects the replenishment of the resource mass of the system, as a result, the available lack of time and resources leads to loss of controllability and at the same time an increase in the probability of destruction. Moreover, if at a certain moment we start implementing anti-crisis measures, then we manage not to lose control over the managed processes and reduce the losses from the crisis and, most importantly, to preserve the stability of the socio-economic system. The feedback of the functions of controllability and destructibility makes it possible to determine the critical point of crisis processes in the socio-economic system. Constant monitoring and evaluation of the position of the critical point contribute to forecasting, early identification of crisis processes, and early preparation for them in order to ensure the sustainable and continuous functioning of socio-economic systems at various levels. The monitoring indicator is the basis for building an anti-crisis monitoring system. Such a parameter should be an integral indicator, represented by a set of variables, each of which reflects the state of the enterprise from different angles. This indicator allows you to assess the probability of destruction of the enterprise and determine the place on the trajectory of its development. One of the options for determining the degradability of the system in the article proposes to use bankruptcy assessment models. The provisions of the theory of crisis management in finding the critical point of crisis processes in socio-economic systems have developed.